Variations in tobacco control in National Dental PBRN practices: the role of patient and practice factors. (5th December 2012) - Ray, Midge N.; Allison, Jeroan J.; Coley, Heather L.; Williams, Jessica H.; Kohler, Connie; Gilbert, Gregg H.; Richman, Joshua S.; Kiefe, Catarina I.; Sadasivam, Rajani S.; Houston, Thomas K.; ,
ABSTRACT: We engaged dental practices enrolled in The National Dental Practice‐Based Research Network to quantify tobacco screening (ASK) and advising (ADVISE); and to identify patient and practice characteristics associated with tobacco control. Dental practices (N = 190) distributed patient surveys that measured ASK and ADVISE. Twenty‐nine percent of patients were ASKED about tobacco use during visit, 20% were identified as tobacco users, and 41% reported being ADVISED. Accounting for clustering of patients within practices, younger age and male gender were positively associated with ASK and ADVISE. Adjusting for patient age and gender, a higher proportion of non‐whites in the practice, preventive services and proportion on public assistance were positively associated with ASK. Proportion of tobacco users in the practice and offering other preventive services were more strongly associated with ASK and ADVISE than other practice characteristics. Understanding variations in performance is an important step toward designing strategies for improving tobacco control in dentistry.